IMPLEMENTASI PROGRAM BANK SAMPAH DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DILINGKUNGAN KOMUNITAS BANK SAMPAH WILAYAH KOTA DEPOK DAN KABUPATEN BOGOR - Sri Setiawati; Rina Aprialliani (JURNAL LENTERA AKUNTANSI, 2019)
This study aims to determine the implementation of the waste bank program in increasing the income of the community in the waste bank community in Depok and Bogor regencies. This study uses qualitative methods, namely research procedures that produce descriptive data in the form of writing and oral from people or observed behavior. Data collection techniques in the form of observation, interviews, and documentation. The results will be used as material for the formulation of strategies, concepts and models of mutually beneficial cooperation (Creditors, Debtors, Municipal Government and Local Government) in accordance with the community typology and business climate in the waste bank community in Depok and Bogor regencies.Keywords: Garbage Bank, Revenue, Depok City and Bogor Regency.